NF-κB in inflammation and renal diseases. Issue 1 (December 2015) - Zhang, Haisong; Sun, Shao-Cong
Abstract Nuclear factor κB (NF-κB) is a family of inducible transcription factors that plays a vital role in different aspects of immune responses. NF-κB is normally sequestered in the cytoplasm as inactive complexes via physical association with inhibitory proteins termed IκBs. In response to immune and stress stimuli, NF-κB members become activated via two major signaling pathways, the canonical and noncanonical pathways, and move to the nucleus to exert transcriptional functions. NF-κB is vital for normal immune responses against infections, but deregulated NF-κB activation is a major cause of inflammatory diseases. Accumulated studies suggest the involvement of NF-κB in the pathogenesis of renal inflammation caused by infection, injury, or autoimmune factors. In this review, we discuss the current understanding regarding the activation and function of NF-κB in different types of kidney diseases.